Resilience as a Mediator Between Parental Acceptance–Rejection and Depressive Symptoms Among University Students in Turkey. (April 2016) - Sart, Zeynep Hande; Börkan, Bengü; Erkman, Fatoş; Serbest, Sevla
Abstract : The authors investigated the mediational role of perceived resilience between perceived parental acceptance–rejection and occurrences of depressive symptoms among 384 undergraduate students in Turkey. Results indicated that resilience fully mediated the relationship between depressive symptoms and maternal rejection, whereas resilience partially mediated the relationship between depressive symptoms and paternal rejection for female undergraduates. Interventions that focus directly on the facilitation of psychosocial adaptation among emerging adults, especially those who experience feelings of rejection by their parents, are discussed.